Financial Inclusion and Demand for Money: a Dynamic Panel Data Approach - Zelin Nurfadia Sidik; Noer Azam Achsani; Syamsul Hidayat Pasaribu (Signifikan: Jurnal Ilmu Ekonomi, 2018)
Financial inclusion is designed to increase the opportunities and society participation in the formal financial institution, especially for unbanked people. Moreover, financial inclusion is one of strategy inclusive economic growth. However, financial inclusion may lead an ineffectiveness of monetary policy. It is because financial inclusion can affect the sensitivity of interest rate, and it could cause instability demand for money. Therefore, the research aims to analyze the impact of financial inclusion on demand for money, reserve money (M0), in 36 countries for the period 2004 to 2014. The method that used is Dynamic Panel Approach. The result shows that financial inclusion stimulates the increase of demand for reserve money (M0) in developed countries. In the other hand, the increasing of financial inclusion could decrease the demand for reserve money (M0) in developing countries.DOI: 10.15408/sjie.v7i2.6838